Handbook of fluoropolymer science and technology - Smith, Dennis W., Jr.; Iacono, Scott T.; Iyer, Suresh S. (Hoboken, New Jersey : Wiley, 2014)
Handbook of Fluoropolymer Science and Technology reviews fluoropolymer platforms of established commercial interest, as well as recently discovered methods for the preparation and processing of new fluorinated materials. Emphasis is placed on emerging technologies in optics, space exploration, fuel cells, microelectronics, gas separation membranes, biomedical instrumentation, and much more. In addition, the book covers the current environmental concerns associated with fluoropolymers, as well as relevant regulations and potential growth opportunities.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Fluoropolymers; Fluoropolymers; Electronic books; Electronic books